Squaramide‐Based Self‐Associating Amphiphiles for Anion Recognition. Issue 8 (5th August 2021) - Kumawat, Lokesh K.; Wynne, Conor; Cappello, Emanuele; Fisher, Peter; Brennan, Luke E.; Strofaldi, Alessandro; McManus, Jennifer J.; Hawes, Chris S.; Jolliffe, Katrina A.; Gunnlaugsson, Thorfinnur; Elmes, Robert B. P.
Abstract: The synthesis and characterisation of two novel self‐assembled amphiphiles (SSAs) SQS‐1 and SQS‐2 are reported. Both compounds, based on the squaramide motif, were fully soluble in a range of solvents and were shown to undergo self‐assembly through a range of physical techniques. Self‐assembly was shown to favour the formation of crystalline domains on the nanoscale but also fibrillar film formation, as suggested by SEM analysis. Moreover, both SQS‐1 and SQS‐2 were capable of anion recognition in DMSO solution as demonstrated using 1 H NMR and UV/Vis absorption spectroscopy, but displayed lower binding affinities for various anions when compared against other squaramide based receptors. In more competitive solvent mixtures SQS‐1 gave rise to a colourimetric response in the presence of HPO4 2− that was clearly visible to the naked eye. We anticipate that the observed response is due to the basic nature of the HPO4 2− anion when compared against other biologically relevant anions. Abstract : Sticky squaramides : Two squaramide‐based self‐assembled amphiphiles (SSAs) are reported that are capable of colorimetric anion recognition in both organic and aqueous solution. Although these SSAs displayed lower binding affinities for anions than other squaramide‐based receptors, in competitive aqueous mixtures, they are fully soluble and capable of selective recognition of HPO4 2− in comparison with other biologically relevant anions.